Unexpected shift in marital relationship: Stress and coping strategies among single mothers in Nigeria - Emmanuel, Tosin (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2025)
Purpose – This study investigated the unexpected shift in marital relationships: stress and coping strategies among single mothers in Nigeria. This category of people has been neglected in the background in the scheme of events in Nigeria, and it is alarming that this neglect affects the mental health of single mothers. Method – This qualitative research adopted an interpretive research paradigm. Data were gathered from fifteen (15) single mothers using semi-structured interviews between November 2024 and February 2025. Collected data was deductively analysed based on recurring themes relating to stress and coping strategies of single mothers who were once in a marital relationship. Result – The study found that financial constraints, stigmatization, disinheritance, and assault were the major stressors confronting the well-being of single mothers in Nigeria. In a bid to cope with the breasting adversities negatively affecting single mothers, this study found the exploration of formal and informal support networks, faith-based religious support, remarriage, and seeking therapeutic intervention as coping mechanisms employed by single mothers. Implication – The government, psychologists/therapists, and relevant stakeholders raise awareness of the availability of counselling services that can assist single mothers in overcoming unexpected challenges. Originality/Value – This study considers single mothers living in remote areas, unemployed, on low incomes, and engaged in menial work. By addressing this knowledge gap, professional counsellors, scholars, religious groups, government support groups, Non-governmental organisations, tiers of government, single mothers, and policymakers will greatly benefit from this study. *** Tujuan – Studi ini menyelidiki pergeseran tak terduga dalam hubungan pernikahan: stres dan strategi penanggulangan di kalangan ibu tunggal di Nigeria. Kelompok masyarakat ini telah diabaikan dalam skema peristiwa di Nigeria, dan mengkhawatirkan bahwa pengabaian ini berdampak pada kesehatan mental ibu tunggal. Metode – Penelitian kualitatif ini mengadopsi paradigma penelitian interpretatif. Data dikumpulkan dari lima belas (15) ibu tunggal melalui wawancara semi-terstruktur antara November 2024 dan Februari 2025. Data yang dikumpulkan dianalisis secara deduktif berdasarkan tema-tema yang berulang terkait stres dan strategi koping ibu tunggal yang pernah berada dalam hubungan pernikahan. Hasil – Studi ini menemukan bahwa kendala finansial, stigmatisasi, pengucilan warisan, dan kekerasan merupakan faktor stres utama yang mengancam kesejahteraan ibu tunggal di Nigeria. Dalam upaya mengatasi kesulitan yang berdampak negatif pada ibu tunggal, studi ini menemukan bahwa eksplorasi jaringan dukungan formal dan informal, dukungan keagamaan berbasis keyakinan, pernikahan kembali, dan mencari intervensi terapeutik merupakan mekanisme koping yang digunakan oleh ibu tunggal. Implikasi – Pemerintah, psikolog/terapis, dan pemangku kepentingan terkait perlu meningkatkan kesadaran tentang ketersediaan layanan konseling yang dapat membantu ibu tunggal mengatasi tantangan tak terduga. Orisinalitas/Nilai – Studi ini mempertimbangkan ibu tunggal yang tinggal di daerah terpencil, pengangguran, berpenghasilan rendah, dan bekerja di bidang pekerjaan kasar. Dengan mengatasi kesenjangan pengetahuan ini, konselor profesional, akademisi, kelompok agama, kelompok dukungan pemerintah, organisasi non-pemerintah, tingkatan pemerintah, ibu tunggal, dan pembuat kebijakan akan sangat diuntungkan dari studi ini.